Association of worrier trait with the risk of Parkinson's disease: a longitudinal study based on 457,180 UK Biobank participants - Li, Rui; Ling, Yitong; Pan, Ao; Cao, Rui; Lyu, Jun; Bi, Wei (Frontiers in Psychology, 2025)
ObjectiveTo explore the potential association between the trait of being a worrier and the likelihood of developing Parkinson's disease (PD).BackgroundWhile extensive research has explored the link between PD and disorders such as depression and anxiety, limited research has been conducted on the association between worry and PD.MethodsThis prospective cohort study utilized data obtained from the UK Biobank, with baseline assessments conducted between 2006 and 2010 and follow-up until July 16, 2023. Multivariable Cox proportional hazards regression analysis was carried out to evaluate the link between worrier trait and the development of PD. Adjustments were made for demographic factors, smoking, PD polygenetic risk scores, alcohol consumption, body mass index, physical activity, stroke, diabetes, hypertension, heart attack, and psychiatric history. Subgroup and sensitivity analyses were additionally conducted to validate the reliability of the outcomes.ResultsOver a mean follow-up period of 13.5 years, 3123 participants (0.68%) out of 457,180 participants [median (IQR) age, 58.00 (50.00, 63.00) years; 54.3% female] developed PD. The incidence of PD was positively linked to worry (log-rank test, P < 0.001). Furthermore, worriers demonstrated a heightened risk of developing PD [hazard ratio (HR) 1.32, 95% CI 1.23–1.42]. Importantly, this link persisted even following adjustments for covariates (fully adjusted model HR 1.27, 95% CI 1.18–1.37). Additionally, when cases within the initial 5 years of follow-up were excluded, the significance of the association persisted (HR: 1.28, 95% CI 1.18–1.38). In subgroup analyses categorized by age, early-onset PD (age < 60 years) showed a stronger association than late-onset PD (age ≥ 60 years; early-onset PD HR 1.32, 95% CI 0.86–2.03; late-onset PD HR 1.13, 95% CI 1.05–1.22).ConclusionThese findings suggest that the worrier trait is consistently associated with a higher risk of developing PD, particularly among young individuals, highlighting the importance of mental wellness.